Triaza-tricyclanos – synthesis of a new class of tricyclic nucleoside analogues by stereoselective cascade cyclocondensation. Issue 10 (21st February 2023) - Bege, Miklós; Herczeg, Mihály; Bereczki, Ilona; Debreczeni, Nóra; Bényei, Attila; Herczegh, Pál; Borbás, Anikó
Abstract : Conformationally constrained tricyclic morpholino-nucleosides containing three new chirality centers were prepared with full stereoselectivity, through two consecutive hemiaminal-imidazolidine cascade reactions. Abstract : Herein, we report a stereoselective synthesis of a novel type of conformationally constrained nucleoside analogue in which the sugar part is replaced by a new symmetrical tricycle consisting of a morpholine ring condensed with two imidazolidines. 1, 5-Dialdehydes obtained from trityl- and dimethoxytrityl-protected uridine, ribothymidine, inosine, cytidine, adenosine and guanosine by metaperiodate oxidation were reacted with N 1, N 3 -dibenzyl-1, 2, 3-triaminopropane; the latter reactant was produced using a new method that avoids explosive intermediates. Reactions of dialdehydes with propane-triamine via cascade tricyclization resulted in the corresponding triaza-tricyclic derivatives bearing three new stereogenic centers in high yields. Out of the eight possible diastereoisomers, one stereoisomer was formed in each case due to the chiral control of the starting nucleoside-dialdehydes and the steric constraint of the condensed ring system. The absolute configuration of the new stereotriad was determined by X-ray diffraction and NMR experiments. A mechanistic study performed under reductive conditions to trap the presumed bicyclic intermediate showed that the triamine reactant first attacks the 2′-aldehyde group, followed by a rapid bicyclization to form the imidazolidino-morpholine unit.